DEVELOPING JIGSAW MODEL FOR YOUNG LEARNERS; PROMOTING MEANINGFUL AND AGE APPROPRIATE SPEAKING ACTIVITIES - Yosefina Rosdiana Su (Jurnal Pendidikan dan Kebudayaan Missio, 2016)
The project with young learner is not an easy one. When teaching young learners, we constantly have to keep in mind the fact that what we have in front of us is a mixed class with varied abilities, expectations, different level of motivation, knowledge and learning styles. Thus, we need to vary our approaches and offer as much opportunity as possible to make the whole class find something to help them to expand and grow. This article provides some developing speaking activities based on the principles of jigsaw which appropriate with young learners stage of development. The provided stages of activities are designed as simple as possible so that it can be applied by both experience and inexperience English teachers of elementary school to promote the fun and meaningful learning experiences for their young learners.